ChemInform Abstract: Synthesis and Characterization of Some Heteroaromatic Derivatives of 3‐But‐2‐enoyl‐chromen‐2‐one and Their Potential as Antiinflammatory Agents. Issue 18 (17th April 2014) - Dixit, Priyanka; Tripathi, Avinash C.; Saraf, Shailendra K.
Abstract: A variety of novel chromen‐2‐one derivatives containing pyrazole, isoxazole, oxazine and thiazine moieties are synthesized starting from chalcone (V).